Pengaruh Cahaya terhadap Pertumbuhan Tanaman Kacang Hijau pada Percobaan Siswa MI Jamiyatul Mubtadiin - Avini Rahmi Ramadani; Muhammad Suwignyo Prayogo; Rezawati Rohmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of sunlight on the growth of mung bean plants (Vigna radiata) with cotton as the planting medium. The study was conducted using an experimental method, namely comparing the growth of mung bean plants that were exposed to direct sunlight with plants that were placed in the shade. The parameters observed included plant height, number of leaves, and germination rate during a certain period. The results showed that mung bean plants that received sunlight grew faster and had more leaves than plants that did not receive direct light. This shows that sunlight plays an important role in the photosynthesis process that supports plant growth. Thus, it can be concluded that sunlight has a significant effect on the growth of mung bean plants, even though using simple cotton as the planting medium.